2020
DOI: 10.4067/s0717-95022020000400919
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Tyrosine Phosphorylation in Liver and Kidney of Polycystic Ovarian Rats Induced by Letrozole

Abstract: is a drug commonly used for breast cancer treatment since it can decrease estrogen level. In experimental animal, the Letro has been used to induce the polycystic ovarian syndrome (PCOS) model. Tyrosine phosphorylation (TyrPho) is an essential process in various biological functions both normal and abnormal conditions especially reproduction. Although some side effects of Letro are reported, the alterations of TyrPho responsible for liver and kidney functions have never been demonstrated. In this study, the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Dilated sinusoids and neutrophilic infiltration were observed. Similar results were previously reported by Chaiyamoon et al (31) . In addition, in a previous study on androgen Induced model of Polycystic Ovary, the appearance of necrotic foci were observed in the liver histology in addition to the inflammatory infiltration and dilated sinusoids as seen in our results.…”
Section: Discussionsupporting
confidence: 93%
“…Dilated sinusoids and neutrophilic infiltration were observed. Similar results were previously reported by Chaiyamoon et al (31) . In addition, in a previous study on androgen Induced model of Polycystic Ovary, the appearance of necrotic foci were observed in the liver histology in addition to the inflammatory infiltration and dilated sinusoids as seen in our results.…”
Section: Discussionsupporting
confidence: 93%
“…To gain our knowledge, CS also changed the functional proteins in liver and kidney especially TyrPho and Hsp 70 proteins. liver and kidney which similar to that stress caused by drug effect called "letrozol" as demonstrated previously (Chaiyamoon et al, 2020). In contrast, a previous study has revealed that the glomerular volume of kidney in CS animals was significantly decreased (Marchon et al, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…In normal condition, TyrPho also has been observed in the rat kidney (Zhang et al, 2008). Moreover, it was documented that the expression of TyrPho proteins in the liver and kidney was totally changed with other functional parameters in stress rats with polycystic ovarian (Chaiyamoon et al, 2020). For chronic stress model in this study, we suggested that TyrPho proteins also play the essential roles for liver and kidney functions although the individual protein need to be further identified and characterized to elucidate the actual mechanism.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation